High-Tech Sector - Definition and Classification Synthesis - Magdalena Łada (Communications of International Proceedings, 2022)
Despite the important role played by the high-tech sector in the modern economy, economics and numerous studies on it, there is no single commonly accepted and used definition. In addition, the relatively short time of its existence and at the same time rapid development also  make it difficult to classify it. The publication concerned the tracing of the development of the definition of the advanced technology sector and the systematization of the classification, which has been subject to modification since the beginning of the sector's existence.
Keywords: High-Tech Sector; High Tech Industry; High Tech Services.